Analisis Perspektif KH. Muhammad Salman Jalil Al-Banjari Dalam Kitab Mukhtasar Al-Awqat Fi Ilmi Al-Miqat Tentang Penentuan Awal Bulan Hijriah - Lutpillah (PT. Saha Kreasi Indonesia, 2025)
The development of science is the result of the return of scholars to Indonesia from Makkah and the Middle East. From then on, several falak figures were born with their works with various calculation methods and continue to grow until now. One of the scholars known as a falak expert is KH. Muhammad Salman Jalil- Al-Banjari. He is famous as a falak expert in Kalimantan. Departing from this, the author wants to explore KH's thoughts. Muhammad Salman Jalil- al-Banjari in the book Mukhtasar al-Awqat fi ilmi al-Miqat on the determination of the beginning of the Hijri month. Kitab Mukhtasar Al-Awqat Fi Ilmi Al-Miqat is one of the books of falak that has its own method in determining the beginning of the Hijri month, so it is interesting to study the method used by KH. Muhammad Salman Jalil Al-Banjari in determining the beginning of the Hijri month, and the level of accuracy, accuracy in calculating the beginning of the Hijri month in the book. Researchers use a type of library research (Library Research), which examines various library sources such as books, journals, and other sources relevant to the topic studied by making the book Mukhtasar Al-Awqat Fi Ilmi Al-Miqat by KH. Muhammad Salman Al-Banjari as primary data. The results showed that the concept of calculating the beginning of the Hijri month in the book Mukhtasar Al-Awqat Fi Ilmi Al-Miqat by KH. Muhammad Salman Al-Banjari uses the hisab 'urfi method which is an easy, fast and simple calculation system; Because the calculation only takes into account the average travel of celestial bodies without using astronomical data so that it does not consider several things such as those contained in the method of hisab haqiqi taqribi, hisab haqiqi tahqiqi, and contemporary hisab haqiqi, namely lunar azimuth, latitude of place, low horizon, refraction, semi diameter, etc.